Hong Kong's Health System : Reflections, Perspectives and Visions - Bacon-Shone, John; Leung, Gabriel M. (Book collections on Project MUSE., 2006)
This book provides a significant contribution to the discussions about the future of the system. The evidence-driven content draws from the deep expertise and experience of a wide spectrum of contributors, who represent virtually all relevant areas of the health system.